The social impact of structural adjustment in Bolivia - Rainer Thiele (Kiel Institute of World Economics (IfW), 2001)
This paper provides an account of the evolution of poverty and inequality during adjustment in Bolivia, covering the period 1985?99. It turns out that urban poverty declined somewhat after the initial stabilization phase that followed the hyperinflation in 1985. A similar evolution of per capita income suggests a positive impact of growth on urban poverty, although the correlation between the two variables is rather low in international perspective. Urban inequality as measured by the Gini coefficient does not exhibit a clear long-term trend upward or downward, but a rising premium for high-skilled workers indicates increasing disparities in the urban labor market. For rural areas, the scant evidence available points towards persistently high poverty levels and a widening rural-urban gap.
Keywords: D3; I3; O1; 330; inequality; structural adjustment; Bolivia; poverty; Anpassungsprogramm des IWF; Armut; Einkommensverteilung; Bolivien